Fabrication of Hollow Mesoporous Nanosized ZSM‐5 Catalyst with Superior Methanol‐to‐Hydrocarbons Performance by Controllable Desilication. Issue 22 (9th October 2017) - Fu, Tingjun; Qi, Ruiyue; Wan, Weili; Shao, Juan; Wen, John Z.; Li, Zhong
Abstract: This work aims to improve the catalyst lifetime of ZSM‐5 for the methanol‐to‐hydrocarbons conversion by tuning the pore structure and external surface area on nano‐ZSM‐5 (100 nm). Several differently pore‐structured samples were synthesized based on the controllable desilication of nano‐ZSM‐5 by prolonging the alkali‐treatment time and introducing tetrapropylammonium hydroxide (TPAOH) into NaOH solution. 2 h NaOH treatment produced mesoporous ZSM‐5 with well‐maintained interior, and the catalytic lifetime was prolonged from 60 to 127 h along with increased isoparaffins selectivity owing to improved diffusion and accessibility of internal weak acid sites. If prolonging the treating time to 15 h, nano‐ZSM‐5 with initially formed hollow structure (HI‐Z5) was achieved, which shows relatively short lifetime of 85 h and high aromatics selectivity. After a secondary treatment of HI‐Z5 with fresh NaOH solution for 5 h, the formed thin shell and clean interior significantly improved diffusion, and the lifetime increased from 85 to 115 h. The aromatics selectivity was also increased by the enhanced acidity. Mesopores were introduced into the shell of HI‐Z5 after treating it with a freshly mixed solution of NaOH and TPAOH. The external surface area exhibited a 94 % increase, resulting in a high isoparaffins selectivity and a long lifetime of 149 h. Abstract : Well‐maintained interior : Mesoporous nano‐ZSM‐5, hollow nano‐ZSM‐5, and hollow mesoporous nano‐ZSM‐5, all of them fabricated by controllable desilication, perform excellently in the methanol‐to‐hydrocarbons reaction. The hollow mesoporous nano‐ZSM‐5 has the dual advantage of mesopores and hollow structures, exhibiting superior performance.